Seasonal variation in semen quality is not associated with fecundity in the Utah Population Database. (29th June 2022) - Patel, Darshan P.; Cheng, Philip J.; Hanson, Heidi A.; Smith, Ken R.; Aston, Kenneth I.; Pastuszak, Alexander W.; Hotaling, James M.
Abstract: We determine whether a suspected seasonal variability in semen quality affect subsequent live birth rates. This is a retrospective, cohort analysis of men who provided semen analyses as part of fertility workup through a large andrology lab between 1996 and 2013 and corresponding birth rates using the Utah Population Database (UPDB). Semen parameters were analysed including total motile count (TMC), total sperm count, sperm concentration and progressive motility. Corresponding live births reflect those born in the state of Utah and were derived from birth certificate data available in the UPDB. Descriptive statistics were reported along with linear regression analysis with mixed effected models to test for an interaction between seasonal variation in semen quality and birth rates, accounting for age at the time of the semen analysis and abstinence time. A total of 11, 929 patients and 14, 765 semen samples were included. Only 3597 men (39% of men) had one or more values outside the World Health Organization reference range for their semen parameters. Linear regression demonstrated a consistent U‐shaped relationship between TMC, total sperm count, and sperm concentration and season, with spring and winter yielding the highest values with a decline in the summer and fall. 7319 of these males had recorded live births for a total of 13, 502 live births during the study period after a median follow‐up of 7.2 years (IQR: 3.9–11.0). We did not find a significant interaction between specific semen parameters for a specific season and subsequent live births. Semen quality was the highest in the spring and winter, however there was no interaction between seasonal variability in semen quality and subsequent births. This is one of the largest studies describing seasonal variation in semen quality in humans.